ICT Integration in Learning: Perceptions of BICTE Students from Nepal - Adhikari, Samikshya; Adhikari, Devi Prasad (An ENDEAVOUR: Journal of Academia and Research, 2026)
The objective of this research is to explore BICTE student perceptions about using technology as an integrative tool into their education at all campuses of Tribhuvan University located throughout the country of Nepal. Using the Descriptive Survey Design following a positivist paradigm, this research utilized the TPACK framework as its conceptual model. Data collection was accomplished using a structured questionnaire (Likert Scale) delivered online via Google Forms. The study included a sample of 105 BICTE students from 20 different campuses that provided data through completed questionnaires using stratified random sampling. Based on the results, BICTE students were found to demonstrate a high degree of digital self-efficacy through consistent use of personal technology (devices and software) while completing their work. BICTE students believe that the use of information and communication technology (ICT) has had a positive impact on their ability to perform well academically, comprehend course content, participate in academic activities, and prepare for employment after graduation. Additionally, students expressed a high degree of confidence in their ability to use digital tools and a favourable attitude toward learning through ICT-based learning. Although, the most respondents reported that their institutions have not established infrastructure for supporting the use of ICT, provided reliable wireless (Internet) access on all campuses, and provided appropriate technical assistance to ensure success with using ICT. On the other hand, faculty’s ICT integration in teaching process is viewed as adequate but not innovative. Thus, the study highlights a significant gap between students’ readiness and institutional provisions required for the ICT integration in teaching learning process. There is a dire need to upgrade ICT facilities, enhancing technical support, strengthening faculty training in digital pedagogy, and standardizing ICT to fully equip BICTE graduates as technology-savvy future educators.